Stan stosunków Unia Europe]ska-Rosja w XXI wieku - Augustyński, Iwo (Status of EU-Russia Relations in the 21st Century, 2008)
The basis for regulations of EU-Russia relations is Partnership and Cooperation Agreement-PCA underwritten in 1997 for 10 years, with the possibility of prolonging this time. Discussions concerning its prolonging are a good occasion to present EU-Russia affairs in the 21st century. Trade between the two sides developed very rapidly in this period. European export to Russia between 2000 and 2006 increased more than three times and import two times accordingly. Nevertheless, the EU notes deficit in trade with Russia due to import of energy resources. Issues concerning energy contain two elements: European access to Russian deposits and attempts to be independent from Russian energy transportation net. Co-operation in the area of security meets obstacles stemming from differences in realization such issues like democracy and human rights in Russia. Tensions evokes situation in Chechnya, Georgia, Kosovo, and Moldova. Enlargement of the EU created new problems in relations with Russia, for instance, problem with Russian minority in Latvia, Estonia, and Lithuania. It should be stated then, that Russia and the European Union represent dissimilar economic and political systems that cannot be integrated.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 273-282